The outcome of Kasai portoenterostomy after day 70 of life - Liu, Fangran; Yeung, Fanny; Chung, Patrick Ho Yu (Frontiers in Pediatrics, 2022)
Background The age at Kasai portoenterostomy (KPE) was reported to correlate with the prognosis of patients with biliary atresia (BA) and that a late KPE is bounded to be failure. Herewith, we reported the outcome of patients receiving KPE after day 70 of life. In addition, the prognostic indicators were evaluated. Materials and Methods This was a retrospective analysis and all BA patients receiving KPE after day 70 of life in a tertiary centre between 1980 to 2018 were evaluated. Results A total of 164 KPE procedures were performed during the study period and 62 cases were done after day 70 of life which were included in this study. The median follow up period of these patients was 10.6 years (range: 4.5 to 41.5 years). Thirty-nine patients (62.9%) patients were able to achieve jaundice clearance at 6 months after KPE. The NLS rate was 53.2% (n=33) as recorded at the time of writing. There was no statistical difference in the age at KPE between native liver survivors and patients requiring liver transplant. For complications among the native liver survivors (n=33), portal hypertension and recurrent cholangitis were found in 63.6% and 30.3% of these patients. There was also no significant difference in the age at KPE between those who developed portal hypertension and recurrent cholangitis (p=0.451 and p=0.173 respectively). Regarding the prognostic indicators in predicting NLS, pre-KPE bilirubin, alkaline phosphatase (ALP) and gamma-glutamyl transferase (GGT) were significantly higher among patients requiring liver transplant (p=0.012, =0.011 and =0.017 respectively). The bilirubin level at 6 months after KPE was also higher among patients who required liver transplant (p=0.016). Conclusion More than half of the BA patients can survive for 10 years with their native liver despite KPE was performed after day 70 of life. However, they have a higher chance to develop BA-related complications. The level of pre-KPE bilirubin and ductal enzymes as well as post-KPE bilirubin are prognostic indicators to predict NLS.